2015
DOI: 10.1007/s00216-015-8953-2
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in biosensing using magnetic glyconanoparticles

Abstract: In this critical review we discuss the most recent advances in the field of biosensing applications of magnetic glyconanoparticles. We first give an overview of the main synthetic routes to obtain magnetic-nanoparticle-carbohydrate conjugates and then we highlight their most promising applications for magnetic relaxation switching sensing, cell and pathogen detection, cell targeting and magnetic resonance imaging. We end with a critical perspective of the field, identifying the main challenges to be overcome, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 79 publications
(127 reference statements)
0
21
0
Order By: Relevance
“…It was shown that these glyco-NPs are able to selectively target specific receptors [ 61 ]. They have also been examined in glycan biosensors [ 62 , 63 , 64 ], in vivo cell imaging and targeting [ 65 ], vaccine vectors development [ 66 , 67 ], virus detection [ 68 , 69 ] and drug delivery [ 70 ]. Glyco-NPs benefit from having a large geometric surface-to-volume ratio, which means that just one NP is able to offer numerous carbohydrate moieties for the enhancement of biomolecular interactions [ 71 ].…”
Section: Glycan-functionalized Nanoparticles (Nps)mentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that these glyco-NPs are able to selectively target specific receptors [ 61 ]. They have also been examined in glycan biosensors [ 62 , 63 , 64 ], in vivo cell imaging and targeting [ 65 ], vaccine vectors development [ 66 , 67 ], virus detection [ 68 , 69 ] and drug delivery [ 70 ]. Glyco-NPs benefit from having a large geometric surface-to-volume ratio, which means that just one NP is able to offer numerous carbohydrate moieties for the enhancement of biomolecular interactions [ 71 ].…”
Section: Glycan-functionalized Nanoparticles (Nps)mentioning
confidence: 99%
“…A good overview of various routes for the modifications of AuNPs, which could then be applicable to glycan immobilization, is shown in two review papers [ 65 , 93 ].…”
Section: Glycan-functionalized Nanoparticles (Nps)mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they are widely used for the separation of bioactive substances (e.g., proteins, enzymes, and nucleic acids), blood screening, cell separation, and immunoassays [ 3 , 4 ]. For these applications, magnetic materials should be subjected to coating and conjugation with appropriate materials on the surfaces of particles [ 5 , 6 ]. With use of functionalized magnetic particles, a broad range of biosensing systems (e.g., immunoassays) for bioimaging or drug delivery have been developed [ 7 – 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, there have been increased interests in magnetic nanoparticle bio sensing (MNPsB). Due to the external control of the magnetic moment, MNPsB promises to enable high-specificity screening and rapid diagnostics of carcinomas(99)(100)(101)(102)(103).…”
mentioning
confidence: 99%